Eosinophilic fasciitis: clinical characteristics and response to methotrexate. (20th December 2014) - Berianu, Florentina; Cohen, Marc D.; Abril, Andy; Ginsburg, William W.
Abstract Aim To describe our experience with 16 patients with eosinophilic fasciitis (EF) treated in our clinic over 14 years. Methods We retrospectively reviewed the charts of all patients with biopsy‐proven EF. We collected data regarding demographics, clinical presentations, possible triggers, labs, imaging, treatment and response to therapy on follow‐up. Results Eight women and eight men with a mean age of 52 years were included in the study. Three patients related the onset to prior strenuous exercise and one was exposed to vibratory machinery. Fourteen patients had a gradual onset and presented with induration of the skin. Two other patients presented with acute‐onset and significant edema and weight gain. All patients required immunosuppressive therapy. Methotrexate (MTX) was used in all of our patients. The rate of complete remission was 60%. Although the recurrence rate after stopping MTX was 70%, these patients responded well to re‐treatment with MTX. Conclusion We believe that MTX represents an effective treatment option for EF. The rarity of this disease would make a double‐blind controlled trial study difficult to perform.